I know that i have to use L'Hos rule and to take a derevative, but I cant get it.
DO you have to use L'Hospital?
Note that $\displaystyle \frac{5x - 1}{5x + 3} = 1 - \frac{4}{5x + 3}$.
So $\displaystyle \left(\frac{5x - 1}{5x + 3}\right)^{5x + 2} = \left(1 - \frac{4}{5x + 3}\right)^{5x + 2}$
The stuff inside the brackets $\displaystyle \to 1$ as $\displaystyle x \to \infty$.
What does $\displaystyle 1^{5x + 2} \to$ as $\displaystyle x \to \infty$?
read this thread of related interest: http://www.mathhelpforum.com/math-he...te-limits.html
Now read my first reply again.